2020
DOI: 10.33197/jitter.vol6.iss2.2020.373
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Surface Partial Discharge Di Sekitar Antarmuka PCB Pada Pelat-Pelat Elekroda Pada Isolasi Udara Dan Minyak

Abstract: Penggunaan peralatan tegangan tinggi pada konverter elektronik daya atau modul daya memiliki pengaruh terhadap sistem isolasi peralatan yang digunakan. Efek yang dihasilkan adalah pelepasan sebagian atau partial discharge (PD), dimana hal tersebut depengaruhi oleh bentuk tegangan, yang mana fenomena PD ini adalah awal mula terjadinya kegagalan dalam suatu peralatan. Pada penelitian ini dilakukan Pengukuran PD dengan mengacu pada Standar IEC 60270 yang menggunakan metode elektrik sebagai pengukuran yang digunak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…In previous research conducted [5], it was found that the research was carried out using homogeneous electrodes of the plate type with PCB type research media. It is known that in the PCB research media there are cavities or voids so that partial discharges can occur.…”
Section: Effect Of Stem-plate Electrode Media On Partial Discharge Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research conducted [5], it was found that the research was carried out using homogeneous electrodes of the plate type with PCB type research media. It is known that in the PCB research media there are cavities or voids so that partial discharges can occur.…”
Section: Effect Of Stem-plate Electrode Media On Partial Discharge Re...mentioning
confidence: 99%
“…Insulation media, be it solid, liquid or gas, is required to have good quality [4]. The non-uniformity of the electric field on the insulating medium/dielectric will cause the phenomenon of Partial Discharge, which will lead to the failure of the insulation itself [5].…”
Section: Introductionmentioning
confidence: 99%
“…Faktor daya (Cos φ) merupakan suatu konstanra pengali dengan nilai 0 sampai 1, yang menunjukkan seberapa besar daya nyata yang diserap oleh beban resistif dari daya semu yang ada pada suatu beban total. (Ardiansyah & Khayam, 2019c, 2019b, 2019aArdiansyah, Khayam, & Nurdiansyah, 2020;Ardiansyah & Pramudita, 2020;Zuhal, 1995)…”
Section: Ii1 Daya Listrikunclassified